Theobromine inhibits uric acid crystallization. A potential application in the treatment of uric acid nephrolithiasis. - Felix Grases (Public Library of Science (PLoS), 2014)
Purpose To assess the capacity of methylxanthines (caffeine, theophylline, theobromine and paraxanthine) to inhibit uric acid crystallization, and to evaluate their potential application in the treatment of uric acid nephrolithiasis. Materials and methods The ability of methylxathines to inhibit uric acid nucleation was assayed turbidimetrically. Crystal morphology and its modification due to the effect of theobromine were evaluated by scanning electron microscopy (SEM). The ability of theobromine to inhibit uric acid crystal growth on calculi fragments resulting from extracorporeal shock wave lithotripsy (ESWL) was evaluated using a flow system. Results The turbidimetric assay showed that among the studied methylxanthines, theobromine could markedly inhibit uric acid nucleation. SEM images showed that the presence of theobromine resulted in thinner uric acid crystals. Furthermore, in a flow system theobromine blocked the regrowth of post-ESWL uric acid calculi fragments. Conclusions Theobromine, a natural dimethylxanthine present in high amounts in cocoa, acts as an inhibitor of nucleation and crystal growth of uric acid. Therefore, theobromine may be clinically useful in the treatment of uric acid nephrolithiasis.